Evaluation of Financial and Operational Performance at BLU-Status Health Polytechnics: Multiple Case Study of 34 Ministry of Health Polytechnics - Muhammad Rizky Bahy Mu'afa; Dodik Siswantoro (Eduvest - Journal of Universal Studies, 2026)
This study evaluates the financial and operational performance of thirty-four Public Service Agency (BLU) Health Polytechnics over 2022 to mid-2025 within the framework of Government Regulation No. 74 of 2012 and Ministry of Finance Regulation No. 202/PMK.05/2022. The method was a multiple-case qualitative study using within-case and cross-case descriptive analyses of Monitoring of Financial and Operational Performance (MKKO) data, performance contracts, and focus group discussions, followed by descriptive and diagnostic analyses applying the 5 Whys and the 4P/S categories (People, Process, Policy, System). The results show high dependence on single tuition fees, limited diversification of non-tuition revenue, a large share of non-academic expenditures, gaps between revenue and academic cost per student, uneven admissions selectivity, strong graduate tracer coverage but highly varied job placement within six months, unbalanced research productivity and down streaming, and unproportional lecturer and staff ratios and ranks. Policy implications emphasize performance-based governance, minimum shares for academic spending, cost-per-service calculations in the business and budget plan, standardized tracer studies, workforce planning and workload rebalancing, and the acceleration of research down streaming and revenue diversification.